Screening and Evaluation of Osteoporotic Biomarkers in Smoking Individuals in Basrah City, Iraq - Hassan, Fatima Amer; Shari, Falah H.; Jaccob, Ausama Ayob (AL-Kindy College Medical Journal, 2025)
Background: Prolonged cigarette smoking leads to significant bone loss, an independent risk factor for osteoporosis. Currently, there are no effective prevention procedures for this, and the exact mechanisms affecting bone metabolism remain unclear. Objectives: This study aims to (1) identify the differences in measured osteoporotic biomarkers among smokers, which are categorized based on the duration and smoking intensity, (2) identify a statistical correlation between variables and smoking intensity, (3) discuss the possibility of employing the appearance of pain sensations in healthy smokers as a reliable indicator of osteoporosis. Subjects and Methods: A study involved 200 males in Basrah city, aged 20-60 years, who were categorized into long-term heavy smokers (LTHS), long-term light smokers (LTLS), short-term current smokers (STCS), and non-smokers (control). A self-reported questionnaire was used to collect baseline data and smoking history. Serum levels of bone-specific alkaline phosphatase (BALP), parathyroid hormone (PTH), 25-hydroxyvitamin D (25OHD), interleukin 6 (IL-6), osteocalcin (OC), Dickkopf-1 (DKK-1), osteoprotegerin (OPG), and Receptor activator of nuclear factor kappa-B ligand (RANKL) biomarkers were measured using an ELISA technique. Results: statistical analysis for mean age 32± 8 years demonstrated a statistically significant relationship (P<0.05) in education levels, employment status, and type of diet among smoker groups. The prevalence of pain symptoms and pain severity showed (P<0.0001) among smoker groups compared to the control group. Among smokers, IL-6, vitamin D, BALP, OC, DKK-1, OPG, and PTH levels were statistically significant. The RANKL/OPG ratio shows significant differences in LTHS and LTLS. Conclusions: The Basra community’s smoking status is influenced by education, employment state, and dietary profile. The high prevalence of smoking and its negative health effects significantly on osteoporotic biomarkers, and pain prevalence is positively correlated with smoking intensity.